Early and Delayed Rebound Intracranial Hypertension following Epidural Blood Patch in a Case of Spontaneous Intracranial Hypotension. (18th March 2022) - Jafari, Elham; Karaminia, Maryam; Togha, Mansoureh
Abstract : Background . Spontaneous intracranial hypotension (SIH) is a secondary headache that has been attributed to a cerebrospinal fluid (CSF) leak. It may resolve spontaneously or require conservative treatment. An epidural blood patch (EBP) with autologous blood is performed in cases exhibiting an inadequate response to conservative methods. Rebound intracranial hypertension (RIH) can develop following an EBP in up to 27% of patients. It is characterized by a change in the headache features and is often accompanied by nausea, blurred vision, and diplopia. Symptoms commonly begin within the first 36 hours, but could develop over days to weeks. It is important to differentiate this rebound phenomenon from unimproved SIH, as the treatment options differ. Case Presentation . Here, we present an interesting case of a patient with SIH who was treated with EBP and developed both immediate RIH after 24 hours and delayed RIH 3 weeks following EBP. Conclusions . Following EBP for treatment of SIH, new onset of headache having a different pattern and location should always be monitored for the occurrence of RIH. A lumbar puncture should be done if the symptoms of elevated CSF pressure become intolerable or if the diagnosis is uncertain. Lack of early diagnosis and treatment and differentiation from SIH can cause complications and could affect the optic nerves.